Femme Ltda. - Daza, Andrés Mauricio; Clavijo Arboleda, Cristian; Herrera Valencia, Clara Isabel (Universidad Icesi, 2008)
Empresas comerciales; Espíritu empresarial; Bisutería;
Keywords: Economics; Economía; Empresas comerciales; Espíritu empresarial; Bisutería